2017
DOI: 10.1371/journal.pone.0179273
|View full text |Cite
|
Sign up to set email alerts
|

Flight of the bumble bee: Buzzes predict pollination services

Abstract: Multiple interacting factors drive recent declines in wild and managed bees, threatening their pollination services. Widespread and intensive monitoring could lead to more effective management of wild and managed bees. However, tracking their dynamic populations is costly. We tested the effectiveness of an inexpensive, noninvasive and passive acoustic survey technique for monitoring bumble bee behavior and pollination services. First, we assessed the relationship between the first harmonic of the flight buzz (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Byrne et al (1988) showed that the smaller size of homopterous insects has higher wingbeat frequency, and Burkart et al (2011) demonstrated that the frequency of wing beat of bees was in a certain range which was anatomically determined and correlated to the size of the bees. Miller-Struttmann et al (2017) investigated the relationship between the sound characteristics of flight sounds and wing length of bumble bees, and found a negative relationship between wing length and the fundamental frequency of flight sounds of bumble bees. The wing length of V. simillima xanthoptera and A. mellifera are 31.76 mm (Byun et al 2009) and 9.3 mm (Ruttner 1988), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Byrne et al (1988) showed that the smaller size of homopterous insects has higher wingbeat frequency, and Burkart et al (2011) demonstrated that the frequency of wing beat of bees was in a certain range which was anatomically determined and correlated to the size of the bees. Miller-Struttmann et al (2017) investigated the relationship between the sound characteristics of flight sounds and wing length of bumble bees, and found a negative relationship between wing length and the fundamental frequency of flight sounds of bumble bees. The wing length of V. simillima xanthoptera and A. mellifera are 31.76 mm (Byun et al 2009) and 9.3 mm (Ruttner 1988), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…So far, acoustic/vibrational analysis has not been extensively used to detect insects, but our results point to various applications. For example, acoustic/vibrational analysis could be used to replicate the studies of Miller-Struttmann et al (2017), who analyzed the buzzing of bumble bees visiting two alpine forbs to evaluate pollination services, and of Potamitis et al (2015), who analyzed wing beats of insect pests to predict the arrival of the pests. We used only a single microphone, but placing multiple microphones in a wide range of places would enable us to study animal movements in the field, and evaluate how they use their habitat over a wide range of areas and time periods (Blumstein et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xylocopa varipuncta (carpenter bee) has been identified to carry pollens of exclusive mangroves like, A. alba, L. racemosa, S. caseolaris, S. ovata and R. apiculata in the mangrove community of Setiu Wetlands, Terengganu (Azmi et al, 2012). Bumble bee visited flowers show increased seed set than when plant excluded from it (Miller-Struttmann, 2017). Carpenter bees have long tongue which gathers mainly pollen, but not nectar.…”
Section: Discussionmentioning
confidence: 97%